The Effect of Whitening and Daily Dentifrices on Red Wine Staining in Different Types of Composite Resins - Nantawan Krajangta; Chayanit Angkananuwat; Seelassaya Leelaponglit; Panyapat Saelor; Natthasit Ngamjarrussriwichai; Awiruth Klaisiri (Applied Sciences)
Injectable resin composites offer flowability while providing enhanced mechanical properties, making them suitable for both posterior and anterior restorations. However, their susceptibility to discoloration and the efficacy of toothpaste in removing stains have not been extensively studied. This study aimed to evaluate the color stability of injectable (G-ænial Universal Injectable), flowable (3M™ Filtek™ Supreme Flowable, 3M, St. Paul, MN, USA), and conventional composite (3M™ Filtek™ Z350 XT Universal Restorative, 3M, MN, USA) after red wine exposure and to compare the stain removal efficacy of whitening (Colgate® Optic White™ Volcanic Mineral Whitening Toothpaste, Colgate-Palmolive, Chonburi, Thailand) versus daily (Colgate® Cavity Protection Toothpaste, Colgate-Palmolive, Chonburi, Thailand) dentifrice. Disc-shaped (7 mm in diameter and 2 mm in height) samples (n = 30) in A3 shade were prepared using injectable, flowable, and conventional composites. The samples were polymerized for 40 s on each side using a curing device set at 1500 mW/cm2 and immersed in red wine for 7 days. After staining, they were brushed with either whitening or daily dentifrice using 4950 strokes. Color measurements were taken at baseline (T1), after staining (T2), and after brushing (T3), using a spectrophotometer. Statistical analysis was performed using ANOVA. Results showed that conventional composites exhibited the highest color change (ΔET1-T2 = 5.50) compared to injectable (ΔET1-T2 = 3.60) and flowable composites (ΔET1-T2 = 3.36). While whitening dentifrice facilitated a greater recovery of discoloration in stained samples (ΔET1-T3 = 1.38–3.67) compared to daily dentifrice (ΔET1-T3 = 2.01–4.28), the observed difference was not statistically significant. In conclusion, all composite types are prone to staining from red wine, and both whitening and daily dentifrices show no difference in efficacy in reducing discoloration.